FISCAL POLICIES IN PANDEMIC TIMES: EUROPEAN EXPERIENCES - Gligor Bishev; Aleksandar Stojkov; Fatmir Besimi (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
The pandemic recession was fundamentally different from ordinary recessions, and thus required a different policy response. We review the empirical literature on fiscal consolidation and fiscal multipliers. Then, we assess the impact of fiscal policies on the pace of recovery and public debt sustainability. A premature or a strong fiscal consolidation might result in lower rates of economic growth and elevated public debt as a share of GDP. We critically analyze different adjustment paths across Europe and offer policy-relevant recommendations. The issue is particularly relevant for countries with a strong fiscal stimulus and moderate to high levels of public debt.
Keywords: economic recovery; fiscal stimulus; public debt; sustainability